(untitled) (Global Journal of Medical Research, 2014)
The oral mucosa may be affected by a variety of systemic diseases and oral lesions most often may precede several mucocutaneous or systemic disorders. The systemic basis for many of the oral lesions is not clearly known. One such oral disease which may have a strong systemic basis for its pathogenesis is chronic desquamative gingivitis (CDG). In the literature there are conflicting reports as to the mechanism of pathogenesis of this clinical entity. Some investigators consider this as a unique clinical disease, whereas, others consider it as the gingival manifestation of disease processes having a strong correlation with the fluctuation of female sex hormones. This study was conducted to find out a correlation between circulating levels of serum estrogen (the female sex hormone) and occurrence of CDG in female patients.